Menjaga Kemaluan (Hifzul Furuj) Dalam Al Qur'an Studi Tafsir Tematik - ahmadiy ahmadiy (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2015)
Hifzul Furuj has meaning an implication that adequately extends and reasonably to be observed. Hifzul Furuj contains several moral consequences, that it everlasting being looked after, petted from conduct thhat prohibitted by God as: porn, fee intercourse, free sex, prostitution, and another insult conducts. Hifzul furuj must be comprehended as an inspiration that every person as a creature of perfection and respondent of glory have to ever think up what does exist in universe with their mind comprises cling on themselves. That thing is really an absolute one to be done by regular awakes it human life congruity and universe in stirred convnient one and poised.